Teachers’ problems in teaching speaking to young learners - Putri Ramadhani; Syamsul Bahri Ys (Research in English and Education Journal, 2017)
This study aims to investigate the teachers’ problems in teaching speaking to young learners at Jasmine Education Center. Those problems were gathered from classroom observation and interviewed the teachers.  In order to investigate the teachers’ problems in teaching speaking to young learners, the researcher used qualitative study to gather the data in this research. The researcher observed the problems found on two English teachers at Jasmine Education Center. The researcher followed the observation guide from Bryne. Additionally, an interview was intended to find out the teachers’ answers in order to know teachers’ problems in teaching speaking to young learners. The interview guide was taken from Kayi The classroom observation showed that the problems found related to class management which were response towards learners and proper environment in teaching and learning process. The answers of the interviews, the researcher found that the teachers’ problems in time prediction in teaching, the way the teacher commented students’ mistakes and lack of ability in analyzing students’ difficulties in learning. In conclusion, the researcher successfully found the problems on the teachers in teaching speaking to young learners in Jasmine Education Center.